2019
DOI: 10.1590/0034-7167-2017-0657
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self-assessment instrument for the Patient Safety Center

Abstract: Objective: To develop and validate an instrument for the self-assessment of the Patient Safety Centers in health care institutions. Method: Non-experimental methodological study. Divided in the following stages: literature review and construction of the preliminary instrument; content validation by nine professionals with experience in Quality Management and patient safety, who contributed to the adequacy of the items in terms of clarity and relevance; finally, 12 PSC coordinators, which conducted the reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
1
1
0
1
Order By: Relevance
“…Cohen's kappa is a measure for inter -rater reliability which was 0.77 for the Radiotherapy administration Checklist, it signified that percentage of agreement was 77%. These findings are in loop with a study was conducted by Macedo and Bohomol at Patient Safety Centers in health care institutions to validate an instrument for the selfassessment for which Cronbach's alpha was 0.857 and percentage of agreement was 70% [12]. M Knöös and M Ostman conducted a similar study to test the reliability and validity of the Oral Assessment Guide in patients receiving radiotherapy and the inter-rater reliability was >71% indicating a high concordance.30 Likewise, a previous study for the development of a risk assessment tool for the prediction of fall examined percentage of agreement between two observers which was found to be 77% and Cronbach's alpha was 0.75 [13].…”
Section: Discussionsupporting
confidence: 82%
“…Cohen's kappa is a measure for inter -rater reliability which was 0.77 for the Radiotherapy administration Checklist, it signified that percentage of agreement was 77%. These findings are in loop with a study was conducted by Macedo and Bohomol at Patient Safety Centers in health care institutions to validate an instrument for the selfassessment for which Cronbach's alpha was 0.857 and percentage of agreement was 70% [12]. M Knöös and M Ostman conducted a similar study to test the reliability and validity of the Oral Assessment Guide in patients receiving radiotherapy and the inter-rater reliability was >71% indicating a high concordance.30 Likewise, a previous study for the development of a risk assessment tool for the prediction of fall examined percentage of agreement between two observers which was found to be 77% and Cronbach's alpha was 0.75 [13].…”
Section: Discussionsupporting
confidence: 82%
“…An instrument development and validation for the Patient Safety Centers self-assessment in health care institutions exhibited a strong reliability almost equal to the value generated in our study. The Cronbach's alpha value that study showed was 0.857 for their instrument [18]. In another work where a new questionnaire was designed for evaluating software usability in Spanish revealed a Cronbach's alpha of 0.839, an exact match to ours [19].…”
Section: Discussionmentioning
confidence: 90%
“…Os dados obtidos na caracterização do perfil profissional e acadêmico dos juízes corroboram com a informação supracitada ao demonstrar que o equivalente a 70% possui como maior titulação doutorado, TCC e/ou dissertação e/ou tese envolvendo estudos dentre a temática abordada na pesquisa. Os níveis de titulação influem no acréscimo do conhecimento científico dos juízes, favorecendo na criticidade e julgamentos mais robustos e com isso, resultados mais verídicos (Macedo & Bohomol, 2019) O tempo de experiência prática dos especialistas na área estudada, também foi considerado um fator de grande importância e está diretamente relacionado com a capacidade de inferências dos juízes. Foram quantificados no estudo que 91% dos especialistas participantes que abarcavam uma mínima de prática profissional na temática de 3 anos, logo, considerou-se que o tempo referido está dentro das recomendações dos estudiosos sobre validação de conteúdo.…”
Section: Discussionunclassified